IMMU-47. RNA-NANOPARTICLE VACCINES ARE SAFE AND IMMUNOLOGICALLY ACTIVE IN CLIENT-OWNED CANINES WITH TERMINAL GLIOMAS. (11th November 2019) - Carrera-Justiz, Sheila; Stover, Brian; Milner, Rowan; Weidert, Frances; Huang, Jianping; Mitchell, Duane; Mendez-Gomez, Hector; Sayour, Elias
Abstract: BACKGROUND: The lack of appropriate preclinical murine glioblastoma models limits comprehensive toxicity/efficacy evaluation of investigational agents. To overcome this challenge, we evaluated the safety and activity of a new immunotherapeutic technology that we have pioneered (composed of tumor mRNA complexed into a custom lipid-nanoparticle formulation) in client-owned canines (pet dogs) diagnosed with malignant gliomas. OBJECTIVE/ METHODS: Canine malignant gliomas were biopsied for generation of personalized tumor mRNA loaded into our custom lipid-nanoparticle (NP) vector. The patients received RNA-NPs intravenously beginning two weeks after their biopsy once weekly (x3) and no other anti-tumor therapeutic interventions. RESULTS: Within a few hours after administration, tumor specific RNA-NPs elicited margination of peripheral blood mononuclear cells, which increased in the subsequent days/weeks post-treatment; suggesting that RNA-NPs mediate lymphoid honing of immune cell populations before egress. RNA-NPs also elicited increased: 1) serum interferon-α that spiked at 2 hours; 2) CD80 and MHCII on CD11c + cells (demonstrating activation of peripheral DCs); and 3) interferon-γ  + T-cells (i.e. activated T-cells). After receiving weekly RNA-NPs (×3), the canines had a steady course. Aside from low-grade fevers on the vaccination days, personalized tumor RNA-NPs (1x) were well tolerated with stable blood counts, chemistries, and renal/liver function tests. All patients assessed developed immunologic response with pseudoprogression or stable/smaller tumors by MRI. Although we have treated a small cohort, we have observed improvement in median/overall survival in all canine patients with terminal gliomas receiving RNA-NPs (compared with historical controls). CONCLUSION: RNA-NPs were feasible, safe and immunologically active in client-owned canines with terminal gliomas. We have not appreciated significant toxicities in canines that would preclude investigation in humans at 1x dosing. Although these results need to be validated in larger canine data sets, these results suggest safety and activity of tumor specific RNA-NPs in canines with terminal gliomas.